2015
DOI: 10.1371/journal.pgen.1005302
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNAs Mediate the Rapid Adaptation of Escherichia coli to Oxidative Stress

Abstract: Translational systems can respond promptly to sudden environmental changes to provide rapid adaptations to environmental stress. Unlike the well-studied translational responses to oxidative stress in eukaryotic systems, little is known regarding how prokaryotes respond rapidly to oxidative stress in terms of translation. In this study, we measured protein synthesis from the entire Escherichia coli proteome and found that protein synthesis was severely slowed down under oxidative stress. With unchanged translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(142 citation statements)
references
References 67 publications
10
130
2
Order By: Relevance
“…However, it is possible that cleavage of RNAs essential for translation similarly confers protection by inhibiting cell growth, as proposed previously by other groups (8,16,17,33). Consistent with this proposal, E. coli rapidly responds to oxidative stress by downregulating translation via tRNA degradation (34). It is also possible that the vapBC genes can prevent bacteriophages from spreading in cell populations by inducing so-called ‘abortive infection’ that has been described for type III TA modules also encoding inhibitors of translation (35,36).…”
Section: Discussionmentioning
confidence: 67%
“…However, it is possible that cleavage of RNAs essential for translation similarly confers protection by inhibiting cell growth, as proposed previously by other groups (8,16,17,33). Consistent with this proposal, E. coli rapidly responds to oxidative stress by downregulating translation via tRNA degradation (34). It is also possible that the vapBC genes can prevent bacteriophages from spreading in cell populations by inducing so-called ‘abortive infection’ that has been described for type III TA modules also encoding inhibitors of translation (35,36).…”
Section: Discussionmentioning
confidence: 67%
“…histolytica [25]. It has been suggested that oxidation of components of the parasite’s translation machinery (e.g., ribosomal proteins, elongation factors) [25], and enzymatic down-regulation of almost all tRNA species [31] are responsible for reduced protein biosynthesis during H 2 O 2 exposure. Our data show that phosphorylation of eIF2α may also contribute to changes in gene expression and protein biosynthesis during oxidative stress in the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…This finding, together with the finding that the kinetics of tRNA decay upon amino acid starvation are similar in wild-type E. coli and a relA mutant, suggests that tRNA instability is not a unique consequence of the stringent response, but may occur as a general response to stresses that reduce translation. 14 The argument is supported by a recent report of extensive tRNA degradation during oxidative stress, 30 which causes stalling of ribosomes at 8-oxoG residues in the mRNA 31 and thereby also limits the pool of functionally intact mRNA available for translation. Since the capacity to synthesize new protein is severely reduced during amino acid starvation, a tRNA-degradation mechanism that depends on synthesis of new protein may not be feasible.…”
Section: A Demand-based Model For Trna Degradationmentioning
confidence: 91%
“…The recent studies mentioned above 14,30 suggest that tRNA degradation could play an important, but hitherto overlooked, role in the bacterial stress response to amino acid starvation as well as other stresses that affect the availability of substrates for translation. Many questions about the process and the importance of tRNA degradation during stress conditions remain to be answered.…”
Section: Effectors Of Trna Degradationmentioning
confidence: 99%